1994
DOI: 10.1203/00006450-199408000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone-Releasing Hexapeptide Is a Potent Stimulator of Growth Hormone Gene Expression and Release in the Growth Hormone—Releasing Hormone—Deprived Infant Rat

Abstract: The growth hormone-releasing hexapeptide (GHRP-6) specifically stimulates growth hormonc (GH) secretion in several animal species and humans. The mechanism of action of GHRP-6 is largely unknown, although experimental evidence indicates that it may modulate growth hormone-releasing hormone (GHRH) and somatostatin actions at the pituitary or hypothalamic level. To gain more insight into the mechanism(s) of action of GHRP-6, we studied the infant rat, an animal model highly responsive to GH-releasing stimuli. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
1
11
1
1
Order By: Relevance
“…A similar pattern had been demonstrated in the early phases of hexarelin administration in old dogs, in which, however, even during the off-periods of the peptide treatment, baseline GH concentrations remained higher than pretreatment values (18). In infant GHRH-deprived rats, treatment with hexarelin for 3 or 5 days increased pituitary GH mRNA (35), whereas, given for 5-10 days to young 'intact' adult rats, it was ineffective in this context (36). Also worth noting in this context is that, in young GHRH-deprived rats, a 10-day treatment with hexarelin increased the expression of its own receptors in the pituitary (R Nass & A Torsello, unpublished results).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A similar pattern had been demonstrated in the early phases of hexarelin administration in old dogs, in which, however, even during the off-periods of the peptide treatment, baseline GH concentrations remained higher than pretreatment values (18). In infant GHRH-deprived rats, treatment with hexarelin for 3 or 5 days increased pituitary GH mRNA (35), whereas, given for 5-10 days to young 'intact' adult rats, it was ineffective in this context (36). Also worth noting in this context is that, in young GHRH-deprived rats, a 10-day treatment with hexarelin increased the expression of its own receptors in the pituitary (R Nass & A Torsello, unpublished results).…”
Section: Discussionsupporting
confidence: 76%
“…In our present study, baseline GH concentrations were not different at the three periods of hexarelin challenge, which would indicate that the ability of GHRP to prime the pituitary was confined to GH release, and did not involve GH synthesis. The enhanced GH responsiveness to hexarelin, present in both rats (35) and dogs (this study and (18)) during the initial phase of treatment has not been reported previously in humans (27,37,38). Although difficult to interpret, this discrepancy may be due to the higher sensitivity of humans than rats and dogs to the GH-releasing activity of the GHRPs, an event for which no clear explanation is available at present.…”
Section: Discussioncontrasting
confidence: 47%
“…Unlike GHRH, GHS and ghrelin induce GH gene expression only upon prolonged delivery to the infantile rat in vivo or to somatotropes in vitro (42,54). Thus model parameters in the adult animal include GHS-dependent stimulation of GH secretion but not de novo GH synthesis.…”
Section: Ghrelin and Gh Network: Basis Of Model Structurementioning
confidence: 99%
“…The minimally effective dose of ghrelin in chickens in vitro (10 9 M) is, however, higher than that (10 11 M) required to provoke GH release in some studies with rat pituitary cells (Yamazaki et al 2002), although it is comparable with that in other studies (Kojima et al 1999). Other GH secretagogue receptor agonists also promote GH release from rat pituitary tissues (Locatelli et al 1994) and a pituitary site of ghrelin action is undoubtedly involved, despite the finding by Pinilla et al (2003) that ghrelin was ineffective in inducing GH release from the pituitaries of prepubertal rats at concentrations of 10 9 to 10 7 M, concentrations that were effective for GHRH.…”
Section: Discussionmentioning
confidence: 85%